Age–Sex Class Variation in the Activity Budget and Diet of Rhinopithecus bieti in Association with Monthly Temperature - Jacob B. Kraus; Zhi Pang Huang; Yan Pang Li; Liang Wei Cui; Shuang Jin Wang; Jin Fa Li; Feng Liu; Yun Wang; Karen B. Strier; Wen Xiao (International Journal of Primatology, 2026)
The energy and nutrient costs associated with body mass, age, and sex can influence variation in primate behavior and diet. However, comparatively little is known about how these factors affect the behavioral and dietary flexibility of Asian colobines in response to intra-annual climate shifts. We collected data on an isolated population of black-and-white snub-nosed monkeys ( Rhinopithecus bieti ) at Mt. Lasha in the Yunling Provincial Nature Reserve, Yunnan, China, using instantaneous and scan sampling across 32 months between May 2008 and August 2016 to assess the association of temperature on the activity budgets and diets among and within age-sex classes. Adult females spent more time feeding, juveniles spent more time moving and less time resting, and adult males spent less time moving and more time resting than other age-sex classes. We did not detect any significant variation in diet across age-sex classes. This population spent more time feeding and less time moving and resting in colder months than in warmer months; however, we only detected these temperature-related effects within age-sex classes for moving and resting, not feeding. This population also spent more time feeding on lichen during colder months than during warmer months, a finding that cannot be explained by temperature-related dietary shifts within age-sex classes because their diets remained stable throughout the year. Our results suggest that intra-annual variation in temperature may amplify the distinct physiological demands among different age-sex classes, leading to greater shifts in activity patterns than in diet composition.

Genome-wide association study of alkali tolerance at germination stage in wheat - Haoran Gu; Zixu Wang; Xiaotong Liu; Haotian Cao; Zixin Zhou; Meishan Zhou; Xinzhi Yang; Han Sun; Ran Qin; Chunhua Zhao; Yongzhen Wu; Fa Cui (Theoretical and Applied Genetics, 2026)

Gene editing and association analysis of circadian clock gene TaPRR59 highlights its importance in yield-related traits in wheat - Jinrong Li; Meijie Zhu; Guimei Hu; Xiaoyue Chen; Huixian Xue; Yuanxun Zhang; Yifan Wang; Ziqi Li; Dengke Xu; Mingjun Zhai; Guangsheng Zhou; Chenxiao Cui; et al. (Theoretical and Applied Genetics, 2026)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

AdaptiveGS: an explainable genomic selection framework based on adaptive stacking ensemble machine learning - Zhen Yang; Mei Song; Xianggeng Huang; Quanrui Rao; Shanghui Zhang; Zhongzheng Zhang; Chenyang Wang; Wenjia Li; Ran Qin; Chunhua Zhao; Yongzhen Wu; Han Sun; et al. (Theoretical and Applied Genetics, 2025)

Isolation and identification of triterpenoid saponins with antiproliferative and hemolytic activities from Camellia oleifera Abel seeds - Jian-Fa Zong; Xiao-Xiang Guo; Kang-Kang Zou; Chuan-Jian Cui; Zi-Hui Hu; Ru-Yan Hou (Phytochemistry, 2025)

Accelerating wheat (Triticum aestivum) proteomics using a tandem digestion approach - Zixin Liu; Zhen Sun; Jiawei Mao; Yue Zhang; Lingping Zhou; Jiahui Wei; Yushen Liu; Luliang Wang; Fangjie Liu; Fa Cui (Journal of Cereal Science, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Cyanide content, nutrient composition, physicochemical properties and sensory quality of flaxseed oil bodies prepared from flaxseeds (Linum usitatissimum L.) treated with different heat treatment methods - Rui Zheng; Hui-Lin Liu; Nan-Nan Cui; Jun-Zhuo Zhou; Xin Sun; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Unlocking the ultrafast laser response and low initiation energy of perchlorate-free tetrazine-based energetic coordination compounds - Hong-Yi Bian; Yun-Fan Yan; Meng Cui; Hao-Hui Xie; Tian-Tian Song; Xiao-Di Guo; Jian-Gang Xu; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2024)

EMS-induced missense mutation in TaCHLI-7D affects leaf color and yield-related traits in wheat - Zixu Wang; Huiyuan Xu; Faxiang Wang; Lingling Sun; Xiangrui Meng; Zhuochun Li; Chang Xie; Huijiao Jiang; Guangshuo Ding; Xinrong Hu; Yuhang Gao; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Genome-wide association study and genomic selection of spike-related traits in bread wheat - Huiyuan Xu; Zixu Wang; Faxiang Wang; Xinrong Hu; Chengxue Ma; Huijiao Jiang; Chang Xie; Yuhang Gao; Guangshuo Ding; Chunhua Zhao; Ran Qin; Dezhou Cui; et al. (Theoretical and Applied Genetics, 2024)

The effect of freeze-thaw action on the dynamic change of supra-permafrost water sources: A stable isotope perspective - Juan Gui; Zongxing Li; Jian Xue; Fa Du; Qiao Cui (Journal of Environmental Management, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

Optimization of ultrasound-assisted extraction of glycyrrhizic acid and glabridin from Glycyrrhiza glabra L. using response surface methodology and development of a green analytical method - Ye-fei Liang; Qing Wen; Zhen-fei Yang; Cui-qin Li; Fa-rong Li (Sustainable Chemistry and Pharmacy, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Copper Azide-based Complexes without Repulsive Steric Clashes between Azides for Advanced Primary Explosives - Yun-Fan Yan; Qian-You Wang; Meng Cui; Hong-Yi Bian; Yong-Fang Han; Jian-Gang Xu; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2023)

Influence of Evaporating Under the Clouds on the Precipitation Stable Isotope in the Transition Zone Between Tibetan Plateau and Arid Region of China - Juan Gui; Zongxing Li; Fa Du; Baijuan Zhang; Jian Xue; Qiao Cui (Chinese Geographical Science, 2023)

QTL Detection for Internode Component Index in Wheat Using a RIL Mapping Population - Ran Qin; Tianhang Ma; Mingsu Cao; Xijian Liu; Xiaohan Zhou; Guimei Hu; Wen Zhong; Xiaohui Sun; Jingguo Xiao; Jiajin Dong; Wenchao Kong; Chunhua Zhao; et al. (Plant Molecular Biology Reporter, 2023)

Regional differences in gully network connectivity based on graph theory: a case study on the Loess Plateau, China - Jian-hua Cheng; Lan-hua Luo; Fa-yuan Li; Lu-lu Liu; Ling-zhou Cui (Journal of Mountain Science, 2023)

QTL detection for internode diameter and its association with yield-related traits in wheat - Haitao Yu; Yanan Liu; Zongfeng Zou; Xusheng Sun; Jinshan Zhang; Shun Song; Lijie Wang; Ran Qin; Han Sun; Fa Cui; Chunhua Zhao; Shubing Shi (Cereal Research Communications, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The brassinosteroid biosynthesis gene TaD11-2A controls grain size and its elite haplotype improves wheat grain yields - Huiyuan Xu; Han Sun; Jiajin Dong; Chengxue Ma; Jingxue Li; Zhuochun Li; Yihuan Wang; Junqi Ji; Xinrong Hu; Meihui Wu; Chunhua Zhao; Ran Qin; et al. (Theoretical and Applied Genetics, 2022)

Fine mapping of QFlw-5B, a major QTL for flag leaf width in common wheat (Triticum aestivum L.) - Chunhua Zhao; Xijian Liu; Hongwei Liu; Wenchao Kong; Zhuochao Zhao; Shengren Zhang; Saining Wang; Yingzi Chen; Yongzhen Wu; Han Sun; Ran Qin; Fa Cui (Theoretical and Applied Genetics, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

Sterols and triterpenoids from Ganoderma lucidum and their reversal activities of tumor multidrug resistance - Min Wu; Cui-e Shen; Qiao-fa Lin; Jin-yi Zhong; Yan-fei Zhou; Ben-chen Liu; Jian-hua Xu; Zhi-qiang Zhang; Peng Li (Natural Product Research, 2022)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Detailed Analysis of Lipids in Edible Viscera and Muscles of Cooked Crabs Portunus trituberculatus and Portunus pelagicus - Ting Lu; Yan Shen; Guo-Xin Cui; Fa-Wen Yin; Zhuo-Liang Yu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2020)

Physical information of 2705 PCR-based molecular markers and the evaluation of their potential use in wheat - Chunhua Zhao; Han Sun; Chunhui Guan; Junpeng Cui; Qianqian Zhang; Mengmeng Liu; Mengna Zhang; Qifan Guo; Yuzhu Hou; Mingjie Xiang; Xiaomin Jiang; Xiulong Luo; et al. (Journal of Genetics, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Identification of QTL regions for seedling root traits and their effect on nitrogen use efficiency in wheat (Triticum aestivum L.) - Xiaoli Fan; Wei Zhang; Na Zhang; Mei Chen; Shusong Zheng; Chunhua Zhao; Jie Han; Jiajia Liu; Xilan Zhang; Liqiang Song; Jun Ji; Xigang Liu; et al. (Theoretical and Applied Genetics, 2018)

QTL for flag leaf size and their influence on yield-related traits in wheat - Chunhua Zhao; Yinguang Bao; Xiuqin Wang; Haitao Yu; Anming Ding; Chunhui Guan; Junpeng Cui; Yongzhen Wu; Han Sun; Xingfeng Li; Dongfeng Zhai; Linzhi Li; et al. (Euphytica, 2018)

Characterization of the temporal and spatial expression of wheat (Triticum aestivum L.) plant height at the QTL level and their influence on yield-related traits - Na Zhang; Xiaoli Fan; Fa Cui; Chunhua Zhao; Wei Zhang; Xueqiang Zhao; Lijuan Yang; Ruiqing Pan; Mei Chen; Jie Han; Jun Ji; Dongcheng Liu; et al. (Theoretical and Applied Genetics, 2017)

A Novel Wheat Nicotianamine Synthase Gene, TaNAS-D, Confers High Salt Tolerance in Transgenic Arabidopsis - Jie Han; Wei Zhang; Lijing Sun; Qiannan Su; Zijing Li; Xiaoli Fan; Na Zhang; Ruiqing Pan; Fa Cui; Jun Ji; Hui Li; Junming Li (Plant Molecular Biology Reporter, 2017)

QTL detection for wheat kernel size and quality and the responses of these traits to low nitrogen stress - Fa Cui; Xiaoli Fan; Mei Chen; Na Zhang; Chunhua Zhao; Wei Zhang; Jie Han; Jun Ji; Xueqiang Zhao; Lijuan Yang; Zongwu Zhao; Yiping Tong; et al. (Theoretical and Applied Genetics, 2016)

Alpha-Synuclein Oligomerization in Manganese-Induced Nerve Cell Injury in Brain Slices: A Role of NO-Mediated S-Nitrosylation of Protein Disulfide Isomerase - Bin Xu; Cui-Hong Jin; Yu Deng; Wei Liu; Tian-Yao Yang; Shu Feng; Zhao-Fa Xu (Molecular Neurobiology, 2014)

Influence of dip directions on the main deformation region of layered rock around tunnels - Zhen-dong Cui; Da-an Liu; Fa-quan Wu (Bulletin of Engineering Geology and the Environment, 2014)

Detection of quantitative trait loci (QTLs) for seedling traits and drought tolerance in wheat using three related recombinant inbred line (RIL) populations - Hong Zhang; Fa Cui; Honggang Wang (Euphytica, 2014)

Construction of an integrative linkage map and QTL mapping of grain yield-related traits using three related wheat RIL populations - Fa Cui; Chunhua Zhao; Anming Ding; Jun Li; Lin Wang; Xingfeng Li; Yinguang Bao; Junming Li; Honggang Wang (Theoretical and Applied Genetics, 2014)

Conditional and unconditional QTL mapping of drought-tolerance-related traits of wheat seedling using two related RIL populations - HONG ZHANG; FA CUI; LIN WANG; JUN LI; ANMING DING; CHUNHUA ZHAO; YINGUANG BAO; QIUPING YANG; HONGGANG WANG (Journal of Genetics, 2013)

Conditional QTL mapping of protein content in wheat with respect to grain yield and its components - LIN WANG; FA CUI; JINPING WANG; LI JUN; ANMING DING; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2012)

Signal-purity-spectrum-based colored deconvolution - Guo-Fa Li; Geng-Xin Peng; Ying Yue; Wan-Li Wang; Yong-Fu Cui (Applied Geophysics, 2012)

QTL detection of seven spike-related traits and their genetic correlations in wheat using two related RIL populations - Fa Cui; Anming Ding; Jun Li; Chunhua Zhao; Lin Wang; Xiuqin Wang; Xiaolei Qi; Xingfeng Li; Guoyu Li; Jurong Gao; Honggang Wang (Euphytica, 2012)

‘Candidatus Phytoplasma ziziphi’ associated with Sophora japonica witches’ broom disease in China - Zhan-Cui Yu; Yang Cao; Qun Zhang; De-Fa Deng; Zhen-Yu Liu (Journal of General Plant Pathology, 2012)

Bt rice expressing Cry1Ab does not stimulate an outbreak of its non-target herbivore, Nilaparvata lugens - Yang Chen; Jun-Ce Tian; Wei Wang; Qi Fang; Zunnu Raen Akhtar; Yu-Fa Peng; Hu Cui; Yu-Yuan Guo; Qi-Sheng Song; Gong-Yin Ye (Transgenic Research, 2012)

Transdifferentiation of human adipose-derived stem cells into urothelial cells: potential for urinary tract tissue engineering - Jian-Guo Shi; Wei-Jun Fu; Xiao-Xiong Wang; Yong-De Xu; Gang Li; Bao-Fa Hong; Kun Hu; Fu-Zhai Cui; Yan Wang; Xu Zhang (Cell and Tissue Research, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Wheat kernel dimensions: how do they contribute to kernel weight at an individual QTL level? - FA CUI; ANMING DING; JUN LI; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; XIUQIN WANG; LIN WANG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2011)

Conditional QTL mapping for plant height with respect to the length of the spike and internode in two mapping populations of wheat - Fa Cui; Jun Li; Anming Ding; Chunhua Zhao; Lin Wang; Xiuqin Wang; Sishen Li; Yinguang Bao; Xingfeng Li; Deshun Feng; Lingrang Kong; Honggang Wang (Theoretical and Applied Genetics, 2011)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Analysis of Cry1Ab toxin bioaccumulation in a food chain of Bt rice, an herbivore and a predator - Mao Chen; Gong-yin Ye; Zhi-cheng Liu; Qi Fang; Cui Hu; Yu-fa Peng; Anthony M. Shelton (Ecotoxicology, 2009)